Новый род и три новых рицептных вида семейства Тгоcharnminidae (Foraminifera) - Михалевич, В.И. (Вестник зоологии, 1971)
A description of the new genus Arcoparrella and two new species of this genus is
given on the basis of data of Soviet expeditions. As a result of reinvestigation of the
typical material from the British museum of natural sciences the species Trochammina
nitida Brad y is transferred to the new genus and a description of the new species
Trochammina refered by Brady (1844) also to T. nitida is given.